The predictive role of the TAPSE/sPAP ratio for cardiovascular events and mortality in systemic sclerosis with pulmonary hypertension - de Pinto, Marco; Coppi, Francesca; Spinella, Amelia; Pagnoni, Gianluca; Morgante, Vernizia; Macripò, Pierluca; Boschini, Matteo; Guerra, Anna Francesca; Tampieri, Francesca; Secchi, Ottavio; Orlandi, Martina; Amati, Gabriele; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Reduced TAPSE/sPAP ratio has recently emerged as a predictive parameter risk factor for PH, however its role in SSc has been poorly investigated. The aim of the study was to investigate the prognostic value of the TAPSE/sPAP ratio for the prediction of mortality and cardiovascular events in patients with SSc complicated by PH. A comparison between SSc patients with PAH (SSc-PAH) and those with PH and significant ILD (SSc-PH) was also carried out. Materials and methods A retrospective single-center study in which all patients having SSc—complicated by PH—referring to the Scleroderma-Unit of the AOU Policlinico of Modena, from October 2013 to October 2023 were evaluated. All SSc patients underwent recurrent clinical examination, routine blood chemistry analysis, functional, instrumental evaluation. Results 61 SSc patients (F/M 52/9) were enrolled. During the follow-up, 60.1% of patients experienced at least one cardiovascular event and 62% died. The main causes of death were PH (39.4%) and other heart-related events (39.4%). The TAPSE/sPAP ratio was significantly lower in deceased patients compared to survivors (mm/mmHg 0.3 ± 0.12SD vs. 0.48 ± 0.17SD, p < 0.001). Compared to the SSc-PAH subgroup, the SSc-PH patients had lower survival rates (55.3 ± 31.2 SD months vs. 25 ± 19 SD, p = 0,05). At the multivariate analysis, TAPSE/sPAP ratio <0.32 mm/mmHg, male gender, and the presence of significant ILD were identified as independent predictors of mortality and cardiovascular events. Conclusion Our work confirmed the predictive role of the TAPSE/sPAP ratio for mortality and cardiovascular events in patients with SSc complicated by PH.